GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Assessment of drinking water biofilter health under warm and cold temperatures - Zoé Jeaurond; Isabella Anim; Jedediah Rode; Joshua Elliott; Onita D. Basu (Journal of Water Process Engineering, 2025)

Optimization and prediction of SO42- removal in electrocoagulation process with rotating electrodes using Taguchi and ANN approach - Amit Kumar; D. Basu (Journal of Environmental Chemical Engineering, 2025)

Understanding the relationship between land use/land cover changes and air quality: A GIS-based fuzzy inference system approach - Mohd Zaid; D. Basu (Environmental Monitoring and Assessment, 2024)

Biological pretreatment of organic waste for short-chain fatty acids production: State-of-the-art, advances, challenges and prospectives - Ajay Thapa; Onita D. Basu; Xunchang Fei; Kaushik Venkiteshwaran; Abid Hussain (Chemical Engineering Journal, 2024)

Comparison of electrocoagulation and combined electrocoagulation-electrooxidation treatment for synthetic tannery wastewaters bearing phenolic syntan - Amit Kumar; D. Basu (Water, Air, & Soil Pollution, 2024)

Incorporating high-resolution climate, remote sensing and topographic data to map annual forest growth in central and eastern Europe - Jernej Jevšenak; Marcin Klisz; Jiří Mašek; Vojtěch Čada; Pavel Janda; Miroslav Svoboda; Ondřej Vostarek; Vaclav Treml; Ernst van der Maaten; Andrei Popa; Ionel Popa; Marieke van der Maaten-Theunissen; et al. (Science of The Total Environment, 2024)

Pre-treatment of lignocellulosic biomass: review of various physico-chemical and biological methods influencing the extent of biomass depolymerization - S. Baksi; D. Saha; S. Saha; U. Sarkar; D. Basu; J. C. Kuniyal (International Journal of Environmental Science and Technology, 2023)

Global taxonomic, functional, and phylogenetic diversity of bees in apple orchards - N. Leclercq; L. Marshall; T. Weekers; P. Basu; D. Benda; D. Bevk; R. Bhattacharya; P. Bogusch; A. Bontšutšnaja; L. Bortolotti; N. Cabirol; E. Calderón-Uraga; et al. (Science of The Total Environment, 2023)

Involvement of indoleamine 2, 3-dioxygenase (IDO) and brain-derived neurotrophic factor (BDNF) in the neuroprotective mechanisms of ferulic acid against depressive-like behaviour - Sanchari Basu Mallik; Jayesh Mudgal; Manas Kinra; Susan Hall; Gary D. Grant; Shailendra Anoopkumar-Dukie; Madhavan Nampoothiri; Yuqing Zhang; Devinder Arora (Metabolic Brain Disease, 2023)
Objective: Ferulic acid (FA) is a common food ingredient that is abundantly present in various routinely consumed food and beverages. Like many cinnamic acid derivatives, FA produces wide-ranging effects in a dose-dependent manner and various studies link FA consumption with reduced risk of depressive disorders. The aim of this study was to exploit the neuroprotective mechanisms of FA including indoleamine 2,3-dioxygenase (IDO), brain-derived neurotrophic factor (BDNF), and other pro-inflammatory cytokines by employing lipopolysaccharide (LPS)-induced depressive-like behaviour model. Methods: C57BL/6J male mice were divided into 4 groups consisting of saline (SAL), LPS, FA and Imipramine (IMI). Animals were pretreated orally with FA (10 mg/kg) and IMI (10 mg/kg) for 21 days once daily and all groups except SAL were challenged with LPS (0.83 mg/kg) intraperitoneally on day 21. Results: LPS administration produced a biphasic change in the behaviour of the animals where the animals lost a significant weight and express high immobility time at 24 h. Proinflammatory cytokines including, TNF-α, IL-6, IL-1β, and IFN-γ were significantly increased along with increased lipid peroxidation and reduced BDNF. Furthermore, the increased kynurenine to tryptophan ratio was indicative of elevated IDO activity. Conclusion: The results of this study emphasise that low dose of FA is effective in attenuating depressive-like behaviour by modulating IDO, BDNF and reducing neuroinflammation.

Sprague Dawley rats from different vendors vary in the modulation of prepulse inhibition of startle (PPI) by dopamine, acetylcholine, and glutamate drugs - S.B. Caine; S. Plant; K. Furbish; M. Yerton; E. Smaragdi; B. Niclou; J.M. Lorusso; J.Y. Chang; C. Bitter; A. Basu; S. Miller; C.-Y. Huang; et al. (Psychopharmacology, 2023)
Rationale Rodent vendors are often utilized interchangeably, assuming that the phenotype of a given strain remains standardized between colonies. Several studies, however, have found significant behavioral and physiological differences between Sprague Dawley (SD) rats from separate vendors. Prepulse inhibition of startle (PPI), a form of sensorimotor gating in which a low-intensity leading stimulus reduces the startle response to a subsequent stimulus, may also vary by vendor. Differences in PPI between rat strains are well known, but divergence between colonies within the SD strain lacks thorough examination. Objectives We explored intrastrain variation in PPI by testing SD rats from two vendors: Envigo and Charles River (CR). Methods We selected drugs acting on four major neurotransmitter systems that have been repeatedly shown to modulate PPI: dopamine (apomorphine; 0.5, 1.5, 3.0 mg/kg), acetylcholine (scopolamine; 0.1, 0.5, 1.0 mg/kg), glutamate (dizocilpine; 0.5, 1.5, 2.5 mg/kg), and serotonin (2,5-Dimethoxy-4-iodoamphetamine, DOI; 0.25, 0.5, 1.0 mg/kg). We determined PPI and startle amplitude for each drug in male and female Envigo and CR SD rats. Results SD rats from Envigo showed dose-dependent decreases in PPI after apomorphine, scopolamine, or dizocilpine administration, without significant effects on startle amplitude. SD rats from CR were less sensitive to modulation of PPI and/or more sensitive to modulation of startle amplitude, across the three drugs. Conclusions SD rats showed vendor differences in sensitivity to pharmacological modulation of PPI and startle. We encourage researchers to sample rats from separate vendors before experimentation to identify the most suited source of subjects for their specific endpoints.

Efficacy of nanoparticles against purple blotch (Alternaria porri) of onion - G. Chaithanya; Atul Kumar; D. Vijay; Praveen Kumar Singh; Zakir Hussain; Sudipta Basu; Sandeep Kumar Lal (Indian Phytopathology, 2023)

Elution and disinfection of silver and zinc nanoparticles in co-fired ceramic water filters - Robbie A. Venis; Onita D. Basu (Science of The Total Environment, 2023)

Economic and performance evaluation of electrocoagulation unit for the treatment of hexavalent chromium using Taguchi method - A. Kumar; D. Basu (International Journal of Environmental Science and Technology, 2023)

Parametric optimization of hexavalent chromium removal by electrocoagulation technology with vertical rotating cylindrical aluminum electrodes using Taguchi and ANN model - Amit Kumar; D. Basu (Journal of Environmental Health Science and Engineering, 2023)

Federated Analysis in COINSTAC Reveals Functional Network Connectivity and Spectral Links to Smoking and Alcohol Consumption in Nearly 2,000 Adolescent Brains - Harshvardhan Gazula; Kelly Rootes-Murdy; Bharath Holla; Sunitha Basodi; Zuo Zhang; Eric Verner; Ross Kelly; Pratima Murthy; Amit Chakrabarti; Debasish Basu; Subodh Bhagyalakshmi Nanjayya; Rajkumar Lenin Singh; et al. (Neuroinformatics, 2023)

Ground motion parameters for the 2015 Nepal Earthquake and its aftershocks - Jahnabi Basu; Bhargavi Podili; S. T. G. Raghukanth; D. Srinagesh (Natural Hazards, 2023)

Vulnerable Waters are Essential to Watershed Resilience - Charles R. Lane; Irena F. Creed; Heather E. Golden; Scott G. Leibowitz; David M. Mushet; Mark C. Rains; Qiusheng Wu; Ellen D’Amico; Laurie C. Alexander; Genevieve A. Ali; Nandita B. Basu; Micah G. Bennett; et al. (Ecosystems, 2023)
Watershed resilience is the ability of a watershed to maintain its characteristic system state while concurrently resisting, adapting to, and reorganizing after hydrological (for example, drought, flooding) or biogeochemical (for example, excessive nutrient) disturbances. Vulnerable waters include non-floodplain wetlands and headwater streams, abundant watershed components representing the most distal extent of the freshwater aquatic network. Vulnerable waters are hydrologically dynamic and biogeochemically reactive aquatic systems, storing, processing, and releasing water and entrained (that is, dissolved and particulate) materials along expanding and contracting aquatic networks. The hydrological and biogeochemical functions emerging from these processes affect the magnitude, frequency, timing, duration, storage, and rate of change of material and energy fluxes among watershed components and to downstream waters, thereby maintaining watershed states and imparting watershed resilience. We present here a conceptual framework for understanding how vulnerable waters confer watershed resilience. We demonstrate how individual and cumulative vulnerable-water modifications (for example, reduced extent, altered connectivity) affect watershed-scale hydrological and biogeochemical disturbance response and recovery, which decreases watershed resilience and can trigger transitions across thresholds to alternative watershed states (for example, states conducive to increased flood frequency or nutrient concentrations). We subsequently describe how resilient watersheds require spatial heterogeneity and temporal variability in hydrological and biogeochemical interactions between terrestrial systems and down-gradient waters, which necessitates attention to the conservation and restoration of vulnerable waters and their downstream connectivity gradients. To conclude, we provide actionable principles for resilient watersheds and articulate research needs to further watershed resilience science and vulnerable-water management.

Isolation and identification of arsenic resistant bacteria: a tool for bioremediation of arsenic toxicity - D. Mandal; R. Sonar; I. Saha; S. Ahmed; A. Basu (International Journal of Environmental Science and Technology, 2022)

Evaluation of seasonal variability in magnitude of urban heat islands using local climate zone classification and surface albedo - K. Dutta; D. Basu; S. Agrawal (International Journal of Environmental Science and Technology, 2022)

The DNA Replication, Repair, and Recombination Pathway Genes Modulating Yield and Stress Tolerance Traits in Chickpea - Udita Basu; Akash Sharma; Deepak Bajaj; Naveen Malik; Uday Chand Jha; Hari D. Upadhyaya; Swarup K. Parida (Plant Molecular Biology Reporter, 2022)

Mechanisms and efficacy of disinfection in ceramic water filters: A critical review - R. A. Venis; O. D. Basu (Critical Reviews in Environmental Science and Technology, 2021)

Decentralized Multisite VBM Analysis During Adolescence Shows Structural Changes Linked to Age, Body Mass Index, and Smoking: a COINSTAC Analysis - Harshvardhan Gazula; Bharath Holla; Zuo Zhang; Jiayuan Xu; Eric Verner; Ross Kelly; Sanjeev Jain; Rose Dawn Bharath; Gareth J. Barker; Debasish Basu; Amit Chakrabarti; Kartik Kalyanram; et al. (Neuroinformatics, 2021)

Variation of salinity in the Sundarbans Estuarine System during the Equinoctial Spring tidal phase of March 2011 - Meenakshi Chatterjee; D Shankar; V Vijith; G K Sen; D Sundar; G S Michael; P Amol; Abhisek Chatterjee; P Sanyal; Siddhartha Chatterjee; Anwesha Basu; Saranya Chakraborti; et al. (Journal of Earth System Science, 2021)

Chromium Exposure in Late Gestation Period Caused Increased Levels of Cr in Brain Tissue: Association with Alteration of Activity and Gene Expression of Antioxidant Enzymes of F1 and F2 Generation Mice - Sumita Halder; Rajarshi Kar; Sucharita Chakraborty; Basu D. Banerjee (Biological Trace Element Research, 2021)

Prediction of Ground Motion Intensity Measures Using an Artificial Neural Network - K. P. Sreejaya; Jahnabi Basu; S. T. G. Raghukanth; D. Srinagesh (Pure and Applied Geophysics, 2021)

Continuous exposure to mercury during embryogenesis and chick development affects later survival and reproduction of zebra finch (Taeniopygia guttata) - Cybele Heddle; John E. Elliott; Tanya M. Brown; Margaret L. Eng; Marie Perkins; Niladri Basu; Tony D. Williams (Ecotoxicology, 2020)

Host-Induced Plant Volatiles Mediate Ability of the Parasitoid Microplitis croceipes to Discriminate Between Unparasitized and Parasitized Heliothis virescens Larvae and Avoid Superparasitism - Basu D. Kafle; Tolulope Morawo; Henry Fadamiro (Journal of Chemical Ecology, 2020)

Genome-wide cis-regulatory signatures for modulation of agronomic traits as exemplified by drought yield index (DYI) in chickpea - Akash Sharma; Udita Basu; Naveen Malik; Anurag Daware; Virevol Thakro; Laxmi Narnoliya; Deepak Bajaj; Shailesh Tripathi; V. S. Hegde; Hari D. Upadhyaya; Akhilesh K. Tyagi; Swarup K. Parida (Functional & Integrative Genomics, 2019)

CLAVATA signaling pathway genes modulating flowering time and flower number in chickpea - Udita Basu; Laxmi Narnoliya; Rishi Srivastava; Akash Sharma; Deepak Bajaj; Anurag Daware; Virevol Thakro; Naveen Malik; Hari D. Upadhyaya; Shailesh Tripathi; V. S. Hegde; Akhilesh K. Tyagi; et al. (Theoretical and Applied Genetics, 2019)

Simulation of synoptic features during summer monsoon onset over GWB, India, with CFSv2 coupled model: skill and bias assessment - S. Chaudhuri; P. Mondal; D. Das; F. Khan; D. Basu (Theoretical and Applied Climatology, 2019)

Impact of intra-seasonal oscillations of Indian summer monsoon on biogeochemical constituents of North Indian Ocean - D. Das; M. Chakrabarty; S. Goswami; D. Basu; S. Chaudhuri (Theoretical and Applied Climatology, 2019)

Cadmium level in brain correlates with memory impairment in F1 and F2 generation mice: improvement with quercetin - Sumita Halder; Rajarshi Kar; Sucharita Chakraborty; Swapan K. Bhattacharya; Pramod K. Mediratta; Basu D. Banerjee (Environmental Science and Pollution Research, 2019)

Alteration in cognitive behaviour, brain antioxidant enzyme activity and their gene expression in F1 generation mice, following Cd exposure during the late gestation period: modulation by quercetin - Sumita Halder; Rajarshi Kar; Nilesh Chandra; Archana Nimesh; Ashish K. Mehta; Swapan K. Bhattacharya; Pramod K. Mediratta; Basu D. Banerjee (Metabolic Brain Disease, 2018)

Interplay between adenosine receptor antagonist and cyclooxygenase inhibitor in haloperidol-induced extrapyramidal effects in mice - Devinder Arora; Jayesh Mudgal; Madhavan Nampoothiri; Sanchari Basu Mallik; Manas Kinra; Susan Hall; Shailendra Anoopkumar-Dukie; Gary D. Grant; Chamallamudi Mallikarjuna Rao (Metabolic Brain Disease, 2018)

Ecologically-relevant exposure to methylmercury during early development does not affect adult phenotype in zebra finches (Taeniopygia guttata) - Spencer A. M. Morran; John E. Elliott; Jessica M. L. Young; Margaret L. Eng; Niladri Basu; Tony D. Williams (Ecotoxicology, 2018)

Discussion on “Array-derived rotational seismic motions: revisited” - D. Basu; M. C. Constantinou; A. S. Whittaker (Bulletin of Earthquake Engineering, 2017)

Genetic dissection of plant growth habit in chickpea - Hari D. Upadhyaya; Deepak Bajaj; Rishi Srivastava; Anurag Daware; Udita Basu; Shailesh Tripathi; Chellapilla Bharadwaj; Akhilesh K. Tyagi; Swarup K. Parida (Functional & Integrative Genomics, 2017)

Swarm intelligence and neural nets in forecasting the maximum sustained wind speed along the track of tropical cyclones over Bay of Bengal - S. Chaudhuri; D. Basu; D. Das; S. Goswami; S. Varshney (Natural Hazards, 2017)

Diplomacy for science: strategies to promote international collaboration - Igor Linkov; Sankar Basu; Cathleen Fisher; Nancy Jackson; Adam C. Jones; Maija M. Kuklja; Benjamin D. Trump (Environment Systems and Decisions, 2016)

Tsunami hazard assessment of Indian coast - A. D. Roshan; Prabir C. Basu; R. S. Jangid (Natural Hazards, 2016)

Quercetin Modulates the Effects of Chromium Exposure on Learning, Memory and Antioxidant Enzyme Activity in F1 Generation Mice - Sumita Halder; Rajarshi Kar; Ashish K Mehta; Swapan K Bhattacharya; Pramod K Mediratta; Basu D. Banerjee (Biological Trace Element Research, 2016)

Risk of contralateral breast cancer in BRCA1 and BRCA2 mutation carriers: a 30-year semi-prospective analysis - N. N. Basu; S. Ingham; J. Hodson; F. Lalloo; M. Bulman; A. Howell; D. G. Evans (Familial Cancer, 2015)

Effect of Low-Intensity Microwave Radiation on Monoamine Neurotransmitters and Their Key Regulating Enzymes in Rat Brain - Kanu Megha; Pravin S. Deshmukh; Alok K. Ravi; Ashok K. Tripathi; Mahesh P. Abegaonkar; Basu D. Banerjee (Cell Biochemistry and Biophysics, 2015)

High influx of carbon in walls of agglutinated foraminifers during the Permian–Triassic transition in global oceans - Galina P. Nestell; Merlynd K. Nestell; Brooks B. Ellwood; Bruce R. Wardlaw; Asish R. Basu; Nilotpal Ghosh; Luu Thi Phuong Lan; Harry D. Rowe; Andrew Hunt; Jonathan H. Tomkin; Kenneth T. Ratcliffe (International Geology Review, 2015)

Cyclic Thermo-Mechanical Analysis of Wellbore in Underground Compressed Air Energy Storage Cavern - S. Mohanto; K. Singh; T. Chakraborty; D. Basu (Geotechnical and Geological Engineering, 2014)

Multi‐site downscaling of maximum and minimum daily temperature using support vector machine - V. V. Srinivas; Bidroha Basu; D. Nagesh Kumar; Sanjay K. Jain (International Journal of Climatology, 2014)
Climate change impact assessment studies involve downscaling large‐scale atmospheric predictor variables ( LSAPVs ) simulated by general circulation models ( GCMs ) to site‐scale meteorological variables. This article presents a least‐square support vector machine ( LS‐SVM )‐based methodology for multi‐site downscaling of maximum and minimum daily temperature series. The methodology involves (1) delineation of sites in the study area into clusters based on correlation structure of predictands, (2) downscaling LSAPVs to monthly time series of predictands at a representative site identified in each of the clusters, (3) translation of the downscaled information in each cluster from the representative site to that at other sites using LS‐SVM inter‐site regression relationships, and (4) disaggregation of the information at each site from monthly to daily time scale using k ‐nearest neighbour disaggregation methodology. Effectiveness of the methodology is demonstrated by application to data pertaining to four sites in the catchment of Beas river basin, India. Simulations of Canadian coupled global climate model ( CGCM3 .1/ T63 ) for four IPCC SRES scenarios namely A1B , A2 , B1 and COMMIT were downscaled to future projections of the predictands in the study area. Comparison of results with those based on recently proposed multivariate multiple linear regression ( MMLR ) based downscaling method and multi‐site multivariate statistical downscaling ( MMSD ) method indicate that the proposed method is promising and it can be considered as a feasible choice in statistical downscaling studies. The performance of the method in downscaling daily minimum temperature was found to be better when compared with that in downscaling daily maximum temperature. Results indicate an increase in annual average maximum and minimum temperatures at all the sites for A1B , A2 and B1 scenarios. The projected increment is high for A2 scenario, and it is followed by that for A1B , B1 and COMMIT scenarios. Projections, in general, indicated an increase in mean monthly maximum and minimum temperatures during January to February and October to December.

Rock failure modes under uniaxial compression, Brazilian, and point load tests - A. Basu; D. A. Mishra; K. Roychowdhury (Bulletin of Engineering Geology and the Environment, 2013)

Tidal variations in the Sundarbans Estuarine System, India - MEENAKSHI CHATTERJEE; D SHANKAR; G K SEN; P SANYAL; D SUNDAR; G S MICHAEL; ABHISEK CHATTERJEE; P AMOL; DEBABRATA MUKHERJEE; K SUPRIT; A MUKHERJEE; V VIJITH; et al. (Journal of Earth System Science, 2013)

A Strain-Rate Dependent Clay Constitutive Model with Parametric Sensitivity and Uncertainty Quantification - H. Martindale; T. Chakraborty; D. Basu (Geotechnical and Geological Engineering, 2013)

Forecasting space–time variability of wave heights in the Bay of Bengal: a genetic algorithm approach - Mourani Sinha; A. D. Rao; Sujit Basu (Journal of Oceanography, 2013)

Advanced glycation end products enhance reactive oxygen and nitrogen species generation in neutrophils in vitro - Savita Bansal; Manushi Siddarth; Diwesh Chawla; Basu D. Banerjee; S. V. Madhu; Ashok K. Tripathi (Molecular and Cellular Biochemistry, 2012)

Effect of phosphamidon on convulsive behavior and biochemical parameters: modulation by progesterone and 4′-chlorodiazepam in rats - Vikas Joshi; Tarun Arora; Ashish K. Mehta; Amit K. Sharma; Naveen Rathor; Kapil D. Mehta; Prabha Mahajan; Pramod K. Mediratta; Basu D. Banerjee; Krishna K. Sharma (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Effect of Soil Disturbance on Consolidation By Prefabricated Vertical Drains Installed in a Rectangular Pattern - D. Basu; M. Prezzi; M. R. Madhav (Geotechnical and Geological Engineering, 2010)

Relationships among mercury, selenium, and neurochemical parameters in common loons (Gavia immer) and bald eagles (Haliaeetus leucocephalus) - A. M. Scheuhammer; N. Basu; N. M. Burgess; J. E. Elliott; G. D. Campbell; M. Wayland; L. Champoux; J. Rodrigue (Ecotoxicology, 2008)

A meta-analysis of occupational trichloroethylene exposure and liver cancer - Dominik D. Alexander; Michael A. Kelsh; Pamela J. Mink; Jeffrey H. Mandel; Rupa Basu; Michal Weingart (International Archives of Occupational and Environmental Health, 2007)

Experimental superensemble forecasts of tropical cyclones over the Bay of Bengal - T. S. V. Vijaya Kumar; J. Sanjay; B. K. Basu; A. K. Mitra; D. V. Bhaskar Rao; O. P. Sharma; P. K. Pal; T. N. Krishnamurti (Natural Hazards, 2007)

Transformation and segregation of GFP fluorescence and glyphosate resistance in horseweed (Conyza canadensis) hybrids - Matthew D. Halfhill; Laura L. Good; Chhandak Basu; Jason Burris; Christopher L. Main; Thomas C. Mueller; C. Neal Stewart (Plant Cell Reports, 2007)

Evaluation of a Fluorescent Method for Measuring Cholinesterase Activity in Mammalian Blood and Tissue - C. J. Stamler; Arrieta D. E.; N. Basu; J. D. Henderson; B. W. Wilson; H. Man Chan (Bulletin of Environmental Contamination and Toxicology, 2006)

Molecular pathogenesis of Wilson disease: haplotype analysis, detection of prevalent mutations and genotype–phenotype correlation in Indian patients - A. Gupta; D. Aikath; R. Neogi; S. Datta; K. Basu; B. Maity; R. Trivedi; J. Ray; S. K. Das; P. K. Gangopadhyay; K. Ray (Human Genetics, 2005)

Ecological Monitoring for Assessing the State of the Nearshore and Open Waters of the Great Lakes - Melanie A. Neilson; D. Scott Painter; Glenn Warren; Ronald A. Hites; Ilora Basu; D.V. Chip Weseloh; D. Michael Whittle; Gavin Christie; Richard Barbiero; Marc Tuchman; Ora E. Johannsson; Thomas F. Nalepa; et al. (Environmental Monitoring and Assessment, 2003)

Insulin alone can lead to a withdrawal of meiotic arrest in the carp oocyte - S. Dasgupta; D. Basu; L. Ravi Kumar; S. Bhattacharya (Journal of Biosciences, 2001)

Role of carcinoscorpin, a haemolymph lectin of horseshoe crabCarcinoscorpius rotundacauda as humoral factor - S. Basu Sarbadhikari; D. Datta; R. Bhadra (Journal of Biosciences, 1999)

Genetic and physiological analysis of doubled-haploid, aluminium-resistant lines of wheat provide evidence for the involvement of a 23 kD, root exudate polypeptide in mediating resistance - U. Basu; J. L. McDonald-Stephens; D. J. Archambault; A. G. Good; K. G. Briggs; Taing-Aung; G. J. Taylor (Plant and Soil, 1997)

A cell line from the gill tissues of indian cyprinoid Labeo rohita - P. S. Sathe; A. Basu; D. T. Mourya; B. A. Marathe; S. S. Gogate; K. Banerjee (In Vitro Cellular & Developmental Biology - Animal, 1997)

Use of small mammals (voles) to assess a hazardous waste site at Love Canal, Niagara Falls, New York - M. H. Rowley; J. J. Christian; D. K. Basu; M. A. Pawlikowski; B. Paigen (Archives of Environmental Contamination and Toxicology, 1983)